BIOLUMINESCENCE SYSTEMS - Idrees, N; Siddique, A; Fateh, A; Afzal, N; Ali, I; Javied, MA; Ali, Q; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
Bioluminescence System has been mostly studied in reporter technology. There are forty different bioluminescent systems occurred in nature while there are only seven of these light emitting systems and their biochemical reactions have been studied however the pathway of only two biochemical systems has been understood yet. Here, we have provided an overview for these bioluminescent systems as a tool for researchers working on bioluminescence for better future applications of bioluminescent.